2021
DOI: 10.3389/fgene.2021.749435
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Overlapping Transcript (LEPROT) Is Associated with the Tumor Microenvironment and a Prognostic Predictor in Pan-Cancer

Abstract: Background:Leptin receptor overlapping transcript (LEPROT) is reported to be involved in metabolism regulation and energy balance as well as molecular signaling of breast cancer and osteosarcoma. LEPROT is expressed in various tissue and is suggested to be involved in cancer developments but with contradictory roles. The comprehensive knowledge of the effects of LEPROT on cancer development and progression across pan-cancer is still missing.Methods:The expressions of LEPROT in cancers were compared with corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Both LEPROT and LEPR are upregulated in breast cancer tumor tissues, and LEPR has previously been reported to be associated with poor prognosis in breast cancer ( 81 ). LEPROT may communicate with the TME, thereby regulating inflammatory or immune signals, and has been reported both to affect cancer development and to serve as a potential prognostic marker or a therapeutic target in pan-cancer ( 82 ). In numerous types of cancer, such as lung and prostate cancer, PTGS2 is secreted by CAFs, macrophage type 2 cells and tumor cells, and is therefore reported to have pleiotropic and multifaceted roles in terms of both carcinogenesis and cancer cell resistance to chemotherapy and radiotherapy ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both LEPROT and LEPR are upregulated in breast cancer tumor tissues, and LEPR has previously been reported to be associated with poor prognosis in breast cancer ( 81 ). LEPROT may communicate with the TME, thereby regulating inflammatory or immune signals, and has been reported both to affect cancer development and to serve as a potential prognostic marker or a therapeutic target in pan-cancer ( 82 ). In numerous types of cancer, such as lung and prostate cancer, PTGS2 is secreted by CAFs, macrophage type 2 cells and tumor cells, and is therefore reported to have pleiotropic and multifaceted roles in terms of both carcinogenesis and cancer cell resistance to chemotherapy and radiotherapy ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LEPROT was found to activate the JAK/STAT pathway and may facilitate cancer development ( 20 ). A recent study identified an aberrant expression of LEPROT in 78.9% cancers compared with corresponding normal tissues ( 21 ).…”
Section: Introductionmentioning
confidence: 99%